KESESUAIAN ANTARA MATERI PEMBELAJARAN BAHASA INGGRIS DAN KURIKULUM DI KELAS 3 SD AL-IRSYAD SURAKARTA - Sumayah Sumayah (Universitas Muhammadiyah Surakarta, 2016)
The research was intended to describe the congruence between English learning material and curriculum in the third year in SD Al-Irsyad Surakarta. The problems discussed were 1. What English learning material was 2. What the learning goal was 3. How the congruence between English learning material and the learning goal was.The research is qualitative. It is a library research. The approach used, in this case, was based on the teaching learning principles. The method applied in this research was analytical descriptive that utilizes library research and concentrated the attention on reference sources related to the topic discussed.The result of the research showed that the learning goal was very closely related to the learning material.